Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T02:05:50+01:00
S₁₀₀ = 2175
S₁₀₀ = [(a₁+ a₁₀₀):2]*100 =2175
[(a₁ + a₁+99r):2]*100 = 2175
( 2a₁ +99r ) * 50 = 2175
2a₁ + 99r = 2175 : 50
2a₁ + 99r = 43,5


a₅₁ = 22
a₅₁ = a₁+50r
a₁+50r = 22
a₁ = 22 -50r
Wstawiam a₁= 22 -50r do równania 2a₁ + 99r = 43,5

2*(22-50r) +99r =43,5
44 -100r +99r = 43,5
-r = 43,5 - 44
-r = -0,5
r = 0,5

Obliczam a₁
a₁=22 -50r
a₁ = 22 - 50*0,5 = 22 -25 = -3
a₁ = -3

a₁ = -3
r = 0,5

Obliczam sumę pierwszych 50 wyrazów ciagu
S₅₀ = [(a₁ + a₅₀):2]*50
S₅₀ = [(a₁ + a₁+49r):2] *50
S₅₀ = [(-3 +(-3) + 49*0,5)]*25
S₅₀ = ( -6 + 24,5)*50
S₅₀ = 925

Obliczam teraz sumę a₅₁+a₅₂+...+a₁₀₀
suma a₅₁+a₅₂+...+a₁₀₀ = S₁₀₀ - S₅₀ = 2175 - 925 = 1250

Odp.a₁ = -3, r = 0,5 , a suma a₅₁+a₅₂+...+a₁₀₀ = 1250
1 5 1